Kinetic Isotope Effects During Reduction of Fe(III) to Fe(II): Large Normal and Inverse Isotope Effects for Abiotic Reduction and Smaller Fractionations by Phytoplankton in Culture - S. G. John; E. A. Boyle; B. R. Cunningham; F.‐X. Fu; S. Greene; C. Hodierne; D. A. Hutchins; A. Kavner; A. L. King; A. D. Rosenberg; M. A. Saito; A. Wasson (Geochemistry, Geophysics, Geosystems, 2024)
Abstract Iron stable isotopes (δ56Fe) are a useful tool for studying Earth processes, many of which involve redox transformations between Fe(III) and Fe(II). Here, we present two related experimental efforts, a study of the kinetic isotope effects (KIEs) associated with the reduction of Fe(III)‐ethylenediaminetetraacetic acid (EDTA) to Fe(II), and measurements of the biological fractionation of Fe isotopes by phytoplankton in culture. Reductants tested were ascorbate, hydroxylamine, Mn(II), dithionite, and photoreduction at pH between 5 and 9 and temperatures from 0 to 100°C. Isotope fractionations were very large, and included both normal and inverse KIEs, ranging from −4‰ to +5‰. Experiments were reproducible, yielding similar results for triplicate experiments run concurrently and for experiments run weeks apart. However, fractionations were not predictable, without a clear relationship to reaction rate, temperature, pH, or the reductant used. Acquisition of Fe by eukaryotic phytoplankton also often involves the reduction of Fe(III) to Fe(II). Several species of diatoms and a coccolithophore were tested for Fe isotope fractionation in culture using EDTA, NTA, and DFB as Fe(III) chelating ligands, yielding fractionations from −1.3‰ to +0.6‰. Biological isotope effects were also unpredictable, showing no clear relationship to species, growth rate, or Fe concentration. Variability in Fe isotope fractionation observed in culture may be explained in part by the sensitivity of KIEs. This work has implications for the industrial purification of isotopes, interpretation of natural δ56Fe, and the use of Fe isotopes as a tracer Fe source and biological processes in the ocean and other natural systems.